(untitled) (Journal of Parents and Teachers, 2014)
It’s unavoidable: an ad has to catch the receiver’s attention. And for that, the publicists will use all their tricks. The valuations and perceptions of objects compete more in the market than the objects themselves. To provide a comprehensive education, we must teach to be critical viewers and to value the content of the ads we see daily.